Math, asked by neeturathore2678, 10 months ago

3(2x + 5) - 2(4x + 3) = 5​

Answers

Answered by Anonymous
13

Answer:

heya mate ☺

3(2x + 5) - 2(4x + 3) = 5 \\  \\   = > 6x + 15 - 8x - 6 = 5 \\  \\  =  >  - 2x + 9 = 5 \\  \\  =  >  - 2x = 5 - 9 \\  \\  =  >  - 2x =  - 4 \\  \\  =  > 2x = 4( -  \: and \:  - cancelled) \\  \\  =  > x =  \frac{4}{2}  \\  \\  =  > x = 2

hope it helps u mate

Answered by TheInnocentSoul
4

Answer:

hey

Thanks for asking mate

kEeP SMiLiNg kEeP sHiNiNg

Attachments:
Similar questions